Associations of psychological status and ultrasonic characteristics of thyroid nodules in adults during the COVID-19 pandemic - Lei, Zhengwu; He, Zhongxiang; Mei, Ying; Qi, Xiaoya; Yu, Pingping; Xu, Guoqiong; Cheng, Hongfeng; Bai, Ruixue; Deng, Jing (Frontiers in Psychology, 2023)
Background: The morbidity of thyroid cancer has been increasing in the last decades all over the world. In addition to the more sensitive thyroid nodule screening technology, several social and environmental factors might represent credible candidates for this increase. They include psychological stress, lifestyle-associated risk factors, nutritional deficiencies, and environmental pollutants. Psychological stress had gained high interest as a possible promoter and a modifiable risk factor for thyroid nodules in recent years. The present study was to investigate the clinical characteristics and psychological status of the population during the peak of COVID-19 and assessed the association of psychosocial determinants and the ultrasonic characteristics of thyroid nodules. Methods: In this cross-sectional study, 490 adult subjects who had received at least two doses of COVID-19 vaccine and were not infected with COVID-19, and did not know whether they had thyroid nodules, received thyroid color ultrasound examination and psychological questionnaire survey. Depression, anxiety, and stress were assessed using Depression Anxiety Stress Scales-21. Sleep quality was rated using the Pittsburgh sleep quality index. The characteristics of 243 subjects with thyroid nodules were described and recorded in detail by thyroid color ultrasound, and the correlations between anxiety, depression, sleep quality, clinical indicators, and thyroid nodule ultrasound characteristics were analyzed. Associations between psychological status (mutually adjusted predictors) and ultrasonic characteristics of thyroid nodules were modeled using binary logistic regression controlling for sex, age, BMI, TSH, FT3, and FT4. Results: Depression was positively correlated with thyroid hypoechoic nodule, microcalcification of thyroids nodule, the aspect ratio of thyroid nodule>1, the unclear boundary of thyroids nodule, and the irregular edge of thyroids nodule. Anxiety was positively correlated with the microcalcification of thyroid nodules. Stress was positively correlated with thyroid hypoechoic nodules, microcalcification of thyroid nodules, and the irregular edge of thyroid nodules. Conclusion: This study demonstrates that depression, anxiety, and stress were associated with the morbidity of thyroid nodules and thyroid ultrasound characteristics. During COVID-19, people's negative emotions increased significantly compared to before. Negative emotions might be harmful to thyroid health. Therefore, during periods of high stress, strategies to prevent psychological problems should be implemented to improve thyroid health.